2013
DOI: 10.1021/bi400118m
|View full text |Cite
|
Sign up to set email alerts
|

DNA A-tracts Are Not Curved in Solutions Containing High Concentrations of Monovalent Cations

Abstract: The intrinsic curvature of seven 98-base pair DNA molecules containing up to four centrally located A6-tracts has been measured by gel and capillary electrophoresis as a function of the number and arrangement of the A-tracts. At low cation concentrations, the electrophoretic mobility observed in polyacrylamide gels and in free solution decreases progressively with the increasing number of phased A-tracts, as expected for DNA molecules with increasingly curved backbone structures. Anomalously slow electrophoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 115 publications
(280 reference statements)
3
31
0
Order By: Relevance
“…Three observations suggest that the mobility differences are not due to differences in shape. First, differences in shape are not observed in BGEs containing 300 mM cation (19). Second, previous studies have shown that the translational diffusion constants of small DNA Biophysical Journal 108(9) 2291-2299 oligomers containing the same number of basepairs are independent of the presence or absence of A-tracts, within experimental error (43,45).…”
Section: The Observed Mobilities Are Independent Of Dna Shapementioning
confidence: 84%
See 3 more Smart Citations
“…Three observations suggest that the mobility differences are not due to differences in shape. First, differences in shape are not observed in BGEs containing 300 mM cation (19). Second, previous studies have shown that the translational diffusion constants of small DNA Biophysical Journal 108(9) 2291-2299 oligomers containing the same number of basepairs are independent of the presence or absence of A-tracts, within experimental error (43,45).…”
Section: The Observed Mobilities Are Independent Of Dna Shapementioning
confidence: 84%
“…We have also characterized the dependence of DNA electrophoretic mobilities on the ionic strength of the solution and the charge density of the polyion (49)(50)(51). Finally, we showed that the curvature of A-tract-containing DNA molecules is markedly reduced in solutions containing~200 mM cation, even though monovalent cations are still preferentially localized in the A-tract minor groove (19). Hence, curvature of the DNA helix backbone and the preferential localization of monovalent cations in the A-tract minor groove are not necessarily linked.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Such bends are dynamic and generally quite gradual, covering several helical turns . It has long been known that both the direction and extent of DNA bending depends upon its electrostatic charge and sequence due to variations in stacking between adjacent base pairs . In general, a pyrimidine followed by a purine is more deformable than other dinucleotides, and dinucleotides comprised of adenines and thymines are more anisotropically flexible than those comprised of cytosines and guanines .…”
Section: Introductionmentioning
confidence: 99%